The Internationalization of the Higher Education and its Infrigement as a Fundamental Right. Analysis within Public Policies 1992–2014. The UPTC case - Lizarazo-Aparicio, Carlos Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper aims to analyze from the point of view of the Colombian public policies the internationalization of education and its effects as a right. For that purpose international organizations guidelines of the economic order are determined in the formulation of educational public policies in Colombia; it is established the effects on the right to education and it is prepared a draft of public policy that guarantees the right to education in Colombia. Infrigement of the right to education by educational policies in Colombia has been evidenced specially since 1992, with Law 30, in the various development plans because government programs of each ruler were directed to reduce the State resources, including subsidies that many low-income students benefited. Regarding internationalization, product of globalization, the UPTC tries to emulate the atmosphere of other developed countries in terms of educational quality, portfolio of programs, among others.